EVALUASI EFEKTIVITAS SISTEM PENGENDALIAN INTERN PADA KOPERASI UNIT DESA “X” DI KABUPATEN BANYUMAS - Eko Suyono (Jurnal Ekonomi Dan Bisnis, 2018)
This study aims to evaluate the effectiveness of internal control system at KUD "X" in Banyumas by using COSO 2013 framework as assessment indicators. Selecting a qualitative approach in which data were collected by indepth interviews and observations, this study concludes that internal control components are in accordance with the COSO 2013 framework, i.e., control environment, risk assessment, control activities, information and communications, and monitoring.  Those components of internal control are present and run well on KUD "X" in Banyumas Region. Therefore this study concludes that with reference to the COSO 2013 framework the internal control system of KUD "X" in Banyumas has been effective.   Keywords: COSO 2013, Control Environment, Risk Assessment, Control Activities, Information and Communication, Monitoring